2021
DOI: 10.1186/s42408-021-00100-9
|View full text |Cite|
|
Sign up to set email alerts
|

A review of fire effects across South American ecosystems: the role of climate and time since fire

Abstract: Background Fire is an important driver of ecosystem dynamics worldwide. However, knowledge on broad-scale patterns of ecosystem and organism responses to fires is still scarce. Through a systematic quantitative review of available studies across South America, we assessed fire effects on biodiversity and abundance of different organisms (i.e., plants, fungi, invertebrates, and vertebrates), plant fitness, and soil properties under four climate types, and time since the last fire (i.e., early an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 149 publications
(199 reference statements)
1
26
0
9
Order By: Relevance
“…In addition, our results underline that unburned plots are exclusive habitats for a few galling insects and plants species, suggesting the importance of unburned sites for conservation purposes, particularly considering the scarce cover of unburned native forest in our study area (Argañaraz et al, 2020; Giorgis et al, 2017). In addition, given the high frequency of fire events in the study area (Argañaraz et al, 2020), it would be interesting to delve into the study of these non‐linear relationships between plant and galling insect communities, including additional fire scenarios, different times since the last fires and ideally different fire severities (Giorgis et al, 2021). Moreover, it would be interesting to extend the study of fire to the third trophic level and its interactions, to better understand the effects of fire on these forest ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our results underline that unburned plots are exclusive habitats for a few galling insects and plants species, suggesting the importance of unburned sites for conservation purposes, particularly considering the scarce cover of unburned native forest in our study area (Argañaraz et al, 2020; Giorgis et al, 2017). In addition, given the high frequency of fire events in the study area (Argañaraz et al, 2020), it would be interesting to delve into the study of these non‐linear relationships between plant and galling insect communities, including additional fire scenarios, different times since the last fires and ideally different fire severities (Giorgis et al, 2021). Moreover, it would be interesting to extend the study of fire to the third trophic level and its interactions, to better understand the effects of fire on these forest ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…The total or partial removal of plant biomass by fire triggers successional changes in plant biodiversity and species composition, with consequent implications on the trophic web structure and species interactions (Bowman et al, 2016; He et al, 2019). Immediately after a fire, mobile organisms show different recovery rates, depending on their particular ecology and strategies to cope with fire, such as refuges and recolonisation (Giorgis et al, 2021; Pausas, 2019). Thus, studies about the effects of fire on insects have shown a broad range of responses related to different species traits, such as occupied trophic level, dispersal ability, functional group, and feeding strategy (Carbone et al, 2019; Kral et al, 2017; Moretti et al, 2006; Swengel, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…How may fire frequency be altering dryland's biodiversity at different scales? A very recent study indicated that available information on the fire regime remains limited for the continent [157]. Therefore, studies focused on fire perimeters, in addition to the severity mapping and landscape controls of fires, would help advance our knowledge about fire in drylands and be powerfully supported by LULC maps.…”
Section: Fire Mappingmentioning
confidence: 99%
“…Most of the ecosystems where cacti occur are subject to different natural and anthropogenic disturbances (Goettsch et al 2015). Natural and human-induced fires are among the most important disturbances in the dry ecosystems of the Americas (Bond & Wilgen 1996;Kowaljow et al 2019;Giorgis et al 2021). Indeed, climatological models predict a worldwide increase in fire intensity and frequency because of global climate change (Pausas et al 2004;Wang et al 2015;Andela et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2019; Giorgis et al . 2021). Indeed, climatological models predict a worldwide increase in fire intensity and frequency because of global climate change (Pausas et al .…”
Section: Introductionmentioning
confidence: 99%